Video Games as Tools to Achieve Insight into Cognitive Processes - Walter R Boot (Frontiers Research Topics, 2015)
Though traditionally designed for entertainment, video games are being used more and more by psychologists to understand topics such as skill acquisition, cognitive capacity and plasticity, aging, individual differences, and development. The appeal of using video games over simpler laboratory paradigms partly comes from their ability to present rich and complex cognitive challenges more representative of the demands of the complex everyday tasks we perform outside of the laboratory. However, this complexity also presents a host of methodological and analytic challenges. This Research Topic brings together research using games to explore cognitive processes, with a special focus on the challenges of this approach. Challenges are in terms of design, implementation, or data analysis.